CHEMICAL COMPOSITION AND PHYSICAL CHARACTERISTICS OF BALI CATTLE RATION FED AT NONGAN EVACUATION ZONES RENDANG DISTRICT KARANGASEM REGENCY - B. F., Sudarmin; Suryani, N. N.; Mariani, N. P. (Jurnal Peternakan Tropika, 2019)
Mount Agung eruption, August to December 2017, caused bali cattle to be evacuated. This study aims to compare the chemical composition and physical characteristics of Bali cattle rations before and after in evacuation zones. The first phase was a survey conducted in January to April 2018 on farmers to collect information about botanical composition fed before and after in evacuation zones and sampling feed ingredients (forages and concentrates). The second phase was to analysis in the laboratory from May to June 2018. The ration was made based on observation in evacuation zones and tabulation of data from the questionnaire result. The research variables were chemical compositionof ration ie: dry matter (%), organic matter (%), crude protein (%), crude fiber (%), ether extract (%) and gross energy (kcal/kg) and physical characteristics ie: bulk density (g/ml), water holding capacity (%), and water solubility (%) of the ration. Results showed thatthe chemical composition given after in evacuation zone based on the protein and energy were 13.32% and 3890 kcal/kg. Physical characteristics of ration which includes bulk density, water holding capacity, and water solubility are higher after in evacuation zones. In conclusion, chemical composition based on lower protein and higher energy after in evacuation zones, physical characteristics of ration after in evacuation zone was higher than before. Keywords : chemical composition, bulk density, water holding capacity, water solubility, bali cattle